Till time's last sand a history of the Bank of England, 1694-2013 - Kynaston, David (London Bloomsbury Publishing, 2017)
Not an ordinary bank, but a great engine of state,' Adam Smith declared of the Bank of England as long ago as 1776. The Bank is now over 320 years old, and throughout almost all that time it has been central to British history. Yet to most people, despite its increasingly high profile, its history is largely unknown.
Includes bibliographical references (pages 797-855) and index.
Keywords: Bank of England